Sumber Rezeki Dalam Perspektif Al-Quran dan Hadits - Kaspia, Yola; Tarigan, Azhari Akmal; Syahriza, Rahmi (AGHNIYA : Jurnal Ekonomi Islam, 2024)
This research aims to reveal the meaning of the word Fortune and the doors to obtaining sustenance based on the signs of the Koran. This research includes qualitative descriptive research with a thematic interpretive research format. This research data is secondary. Secondary data is data that contains ideas, ideas and interpretations of interpreters. The results of this research show that the word "sustenance" is mentioned 123 times in the Al-Quran with different fi'il forms, contents and meanings. The meaning of sustenance is everything that is useful that Allah makes lawful, in the form of clothing, food, possessions. That all includes sustenance. Likewise, sons or daughters are included in sustenance. Also included in this are health, hearing and vision. Sources of human sustenance based on God's promises to humans include: sustenance from effort, sustenance from gratitude, sustenance that has been guaranteed, sustenance from istitighfar, sustenance from charity, sustenance from marriage, sustenance from children, and unexpected sustenance.